Application of equilibrium binding model for analysis of conformational transitions in poly(rA)poly(rU) complexes with metal ions - Blagoi, Yu.P.; Egupov, S.A.; Usenko, E.L.; Gladchenko, G.O.; Sorokin, V.A. (Вiopolymers and Cell, 2010)
Aim. The study is aimed at generalization of the previous experimental results on the metal ion (Mg²⁺, Ni²⁺, Cd²⁺) effects on conformation transitions in poly(rA)poly(rU). The objective was to find out how the type of a metal ion-polynucleotide complex influences the phase transitions and to estimate the constants (K) of ions binding to polymers of different structures. Methods. The K values were obtained upon theoretical and experimental transition temperature fitting by the least-square method with the root mean square deviation minimized through the procedure of the gradient descent in the multidimensional space. Results. Calculations of diagrams with Mg²⁺ are shown to permit obtaining satisfactory results if concentration-independent, mean values of constants are used. For Ni²⁺ and Cd²⁺ the concentration dependence of K must be taken into account, especially for high ion contents at which compaction of single-stranded poly(rA) emerges. It was revealed that the main factor responsible for the differences in diagrams with Ni²⁺ and Cd²⁺ is a significant distinction of their constants of binding to poly(rA) and poly(rU). Conclusions. The model theory of equilibrium binding is capable to describe adequately conformation transitions in polynucleotides in the presence of metal ions.